Musicians’ Health and Wellness Resources in Canadian Post-Secondary Music Programs - Tinoco, Carlos; Traube, Caroline; Guptill, Christine (Revue musicale OICRM, 2024)
Research suggests that more than 80% of professional musicians will encounter performance-related health conditions that negatively affect their ability to work. Current literature suggests that these conditions are prevalent amongst post-secondary music students. Existing studies examine a small number of post-secondary music schools who have implemented health promotion courses in their curricula and have demonstrated improvements in self-efficacy and perceived knowledge of health promotion strategies. We sought to examine health promotion and health education offerings in Canadian post-secondary music programs. Members of the new Canadian Network for Musicians’ Health and Wellness (cnmhw) were the focus of this study. Members completed a survey and were then interviewed to further discuss their educational offerings. All the post- secondary institutions examined have health education offerings available to students. Four institutions have courses implemented within their curricula; the other institution has a sizeable selection of health-related initiatives available to students.